Impact of hopelessness on migration intentions of nursing students: a path analysis - Soner Berşe; Emine Karacan; Pelin Zivdir Yeşılyurt; Zeynep Güngörmüş (BMC Nursing)
Abstract Background Brain drain refers to the migration of qualified professionals to developed countries in search of better living and working conditions, and has become a global concern, particularly in the healthcare sector. Migration of highly skilled nurses results in increased workload for the remaining nursing staff, limited access to quality healthcare services, and contributes to disparities in healthcare. Therefore, nursing students represent a critical demographic group for understanding the drivers of brain drain in the healthcare sector. Purpose This study aimed to assess the levels of hopelessness experienced by nursing students in Turkey throughout their education and to examine the impact of hopelessness on their decisions to move abroad. Materials and methods The study was conducted on 795 students enrolled in the nursing departments of two public universities in Gaziantep. Data were collected using a Demographic Data Form, the Beck Hopelessness Scale, and the Attitudes Towards Brain Drain Scale. The data were analyzed using the SPSS 24.0 statistical software. Results 57% of the nursing students considered moving abroad, with 20.2% preferring Germany. The primary reasons for their desire to migrate included poor living conditions (11.1%), economic problems (12.9%), unfavorable working conditions (8.3%), and educational challenges (5.4%). The findings highlight the significant role of future hopelessness in influencing the migration intentions of nursing students. Conclusion More than half of Turkish nursing students consider moving abroad to seek better working conditions, higher living standards, financial gains and educational opportunities, with Germany being their top destination country. Despite low levels of hopelessness observed among the students, the tendency for migration persisted. A retention policy needs to be developed with strategic actions to prevent nurses from migrating to other countries. Clinical trial number not applicable.